2018
DOI: 10.1177/1708538118805623
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of extended endovascular recanalization of 16 consecutive Buerger’s disease patients

Abstract: Objective Buerger’s disease is one of the worst diseases causing peripheral artery occlusions (especially lower extremity) with increased morbidity and mortality. Endovascular treatment of the diseased arteries gains preference over bypass surgery nowadays. Here, we aimed to present the clinical outcomes of 16 consecutive Buerger’s disease patients underwent extended endovascular recanalization which is a new technique to restore direct blood flow to at least one foot artery, with the performance of angioplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
7
0
2
Order By: Relevance
“…Graziani et al and Kacmaz et al reported a 100% limb salvage rate after endovascular recanalization in patients with TAO. 18,19 In our study, we have had patency rates of 66.6% after angioplasty and 56.2% after bypass procedures.…”
Section: Discussionmentioning
confidence: 84%
“…Graziani et al and Kacmaz et al reported a 100% limb salvage rate after endovascular recanalization in patients with TAO. 18,19 In our study, we have had patency rates of 66.6% after angioplasty and 56.2% after bypass procedures.…”
Section: Discussionmentioning
confidence: 84%
“…[ 18 ] Recently advanced less-invasive endovascular treatment is a technically feasible and potentially effective treatment modality for TAO. [ 22 , 28 30 ] However, despite more aggressive and advanced therapeutic options, there remains a high rate of amputations associated with TAO. [ 1 4 ]…”
Section: Discussionmentioning
confidence: 99%
“…[18] Recently advanced less-invasive endovascular treatment is a technically feasible and potentially effective treatment modality for TAO. [22,[28][29][30] However, despite more aggressive and advanced therapeutic options, there remains a high rate of amputations associated with TAO. [1][2][3][4] TAO has been considered to be limited to the small-and medium-sized arteries of the distal extremities affecting younger smokers.…”
Section: Discussionmentioning
confidence: 99%
“…En el tratamiento endovasuclar de la enfermedad de Buerger, se ha determinado, según varios estudios, que la tasa de éxito técnico es alta, del 87,5% (Firat, 2019), 91% (Kacmaz, 2019), 82% (Uyanik, 2021). Y la tasa de salvamento de la extremidad del 100% (Kacmaz, 2019), 92% (Modaghegh, 2017), 87,5% (Rodoplu, 2020), 93,3 % (Uyanik, 2021.…”
Section: Oclusiones Arteriales Infrapoplíteasunclassified
“…En el estudio de Kacmaz (2019), todos los pacientes (16) que fueron intervenidos endovascularmente fueron dados de alta con éxito y sin reportarse ninguna complicación. Los pacientes que presentaron ulceras isquémicas lograron obtener una cicatrización completa de la herida en 3,9 ± 2.…”
Section: Oclusiones Arteriales Infrapoplíteasunclassified